Comparative Analysis of Faired-In Bulb and Bulbous Bow Ram Bow's Bulbous Bow Shape On Total Ship Resistance - Ba Naga, Mohammed Hussein; Nuramalia, Zabrina (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2023)
A General Cargo Ship is a ship that carries various kinds of cargo in the form of goods. The goods transported are usually packaged goods. Using a bulbous bow on the ship's bow is the best alternative. Bulbous bows are installed on ships with high speed to reduce drag, whose nature depends on the function of the block coefficient and Froude number of ships. Ships with particular Cb and Fn can use a Bulbous bow due to considering the advantages of a significant enough resistance reduction, or vice versa. This research is a general cargo ship model with a bulbous bow. They are using the main dimensions of the ship with Length Over All (LOA) 153.45 m, Length Between Perpendicular (LBP) 144.2 m, Length On Load Waterline (LWL) 147.8 m, and Breadth (B) 25.27 m. height (H) 13.5 m, Draft (T) 9.52 m, Speed ​​(V) 14.75 Knots. The magnitude of the resistance and practical power of the ship required to reach a speed of 14.75 knots on a ship with the Faired-in Bulb type obtained from maxsurf 431.9 kN and 4096, 548 HP. For Bulbous bow type Ram Bow ships, the resistance and adequate power obtained are 431.3 kN and 4090,683 Hp. The ship's power using the Bulbous bow Faired-in Bulb is more significant than using the Bulbous bow of the Ram Bow type.